1976
DOI: 10.1093/jnci/56.4.843
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Cultures From Normal and Cancerous Human Tissues2

Abstract: Thirty epithelial cell strains were isolated from human carcinomas and normal epithelial tissues by collagenase digestion and selective removal of fibroblasts with trypsin-Versene. Most strains were obtained from metastatic carcinomas or epithelia of the urinary and intestinal tracts. The success rate for growth of both neoplastic and normal tissues (excluding skin) was 38%. Six of these strains showed gross morphologic and chromosome changes typical of malignant cells. Nine resembled normal epithelium. The ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(69 citation statements)
references
References 0 publications
1
68
0
Order By: Relevance
“…In addition, we observed growth inhibition of LNCaP following long-term NDF treatment, accompanied by morphological changes such as cell clustering, withdrawal of processes, and increased cell ± cell membrane contact. These alterations are consistent with the reversion to an epithelial phenotype (Owens et al, 1976). In order to test this possibility, NDF-stimulated LNCaP will be analysed for increased expression of epithelial-speci®c markers.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, we observed growth inhibition of LNCaP following long-term NDF treatment, accompanied by morphological changes such as cell clustering, withdrawal of processes, and increased cell ± cell membrane contact. These alterations are consistent with the reversion to an epithelial phenotype (Owens et al, 1976). In order to test this possibility, NDF-stimulated LNCaP will be analysed for increased expression of epithelial-speci®c markers.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, eight of the 12 cell lines were found to produce CA19-9, and several produced CEA or DUPAN-2 as well. The four remaining cell lines were characterised mainly by morphological analysis (Lieber et al, 1975;Yunis et al, 1977;Owens et al, 1979;Yamada et al, 1986;Ikeda et al, 1990), which suggested that they originated from pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FHs 74 Int human small intestinal epithelial cells 34 were purchased from ATCC (Manassas, VA) and maintained in Hybri-Care Medium ATCC 46-X supplemented with 30 ng/ml epidermal growth factor (Sigma-Aldrich) and 10% FBS. RIE-1 rat intestinal epithelial cells 35 were maintained in DMEM containing 2 mM L-glutamine, 4500 mg/L glucose and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%